2018
DOI: 10.12973/ijem.4.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Feedback of mDPBL Approach and the Learning Impact towards Computer Networks Teaching and Learning

Abstract: This study presents students' feedback and learning impact on design and development of a multimedia learning in Direct Problem-Based Learning approach (mDPBL) for Computer Networks in Dian Nuswantoro University, Indonesia. This study examined the usefulness, contents and navigation of the multimedia learning as well as learning impacts towards mDPBL approach which used. A total of 276 students who took Computer Networks subject from two different departments participated in this study of a quasi-experiment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Some scholars believe that smart education teaching terminals can accurately perceive students' learning progress, and the intelligent teaching assessment methods must be diversi ed. It uses multimedia network technology to realize online communication and interaction between teachers and students and checks and ll gaps in knowledge to achieve the goal of improving and internalizing knowledge [2,3]. Although the application research results of multimedia computer network education in smart course teaching emerge in an endless stream, to realize the interactivity of smart teaching under the network education platform, it is necessary to promote the reform of teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars believe that smart education teaching terminals can accurately perceive students' learning progress, and the intelligent teaching assessment methods must be diversi ed. It uses multimedia network technology to realize online communication and interaction between teachers and students and checks and ll gaps in knowledge to achieve the goal of improving and internalizing knowledge [2,3]. Although the application research results of multimedia computer network education in smart course teaching emerge in an endless stream, to realize the interactivity of smart teaching under the network education platform, it is necessary to promote the reform of teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…Sung (2015) and Gencer, Gurbulak and Adıguzel (2014) showed that FC model facilitates learning and increases the student-instructor interaction. Winarno, Muthu and Ling (2018) showed that all students reported positive feedbacks on the multimedia learning. They especially find it usefulness, rich in content and easy to navigate.…”
Section: Discussionmentioning
confidence: 91%
“…Vídeo [40], [56], [45], [29], [41] El vídeo es un medio de aprendizaje sobre un determinado tema, cuyo propósito es comprender y analizar los gráficos de objetos en movimiento [40].…”
Section: Estrategias De Retroalimentación Correctiva Escritaunclassified
“…Herramientas multimedia [36], [26], [56], [41] Las herramientas multimedia permiten el desarrollo de actividades académicas, puesto que, el estudiante realiza la interacción con los contenidos, para lograr el aprendizaje y fortalecer sus metas [40]. [34] en su investigación, evidencian el uso de programas informáticos (socrative, moodle, etc), para reforzar los aprendizajes, considerando:…”
Section: Estrategias De Retroalimentación Audiovisualesunclassified